1995
DOI: 10.1346/ccmn.1995.0430202
|View full text |Cite
|
Sign up to set email alerts
|

Layer Charge of the Expandable Component of Illite/Smectite in K-Bentonite as Determined by Alkylammonium Ion Exchange

Abstract: Abstract--The charge of the expandable interlayers in a series of fourteen diagenetic illite/smectites (I/ S) from lower Paleozoic K-bentonites was determined by the alkylammonium ion exchange method. The magnitude (<0.50 equivalents per half formula unit) and characteristic heterogeneous distribution of interlayer charges in eight samples with expandabilities from 70% to about 15% confirm the smectitic character of the expandable interlayers in this range. This result coupled with the lack of a correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Barron et al (1985) and Jakobsen et al (1995) found similar results for rectoritc, although the mica sites in rectorite have a greater charge than illite sites in I/S. XRD analysis of alkylammonium-treated US samples indicates that expandable interlayers in R0-and Rl-ordered I/S have a smectite composition (Lagaly 1979;Cetin and Huff 1995a). The polar 2:1 layer model can account for the chemical variations of fundamental particles as averages of the illite and smectite interlayer sites present in each particle, for example, 20-.& thick particle: Nevertheless, on the basis of TEM and XRD analysis of alkylammonium-treated US samples, several investigators (Vali and Hess 1990;Vali et al 1991;Huff 1995a, 1995b) conclude that expandable interlayers in illitic I/S are not in fact, smectite but vermiculite in charge.…”
Section: Crystal Chemical Structure Of Usmentioning
confidence: 79%
“…Barron et al (1985) and Jakobsen et al (1995) found similar results for rectoritc, although the mica sites in rectorite have a greater charge than illite sites in I/S. XRD analysis of alkylammonium-treated US samples indicates that expandable interlayers in R0-and Rl-ordered I/S have a smectite composition (Lagaly 1979;Cetin and Huff 1995a). The polar 2:1 layer model can account for the chemical variations of fundamental particles as averages of the illite and smectite interlayer sites present in each particle, for example, 20-.& thick particle: Nevertheless, on the basis of TEM and XRD analysis of alkylammonium-treated US samples, several investigators (Vali and Hess 1990;Vali et al 1991;Huff 1995a, 1995b) conclude that expandable interlayers in illitic I/S are not in fact, smectite but vermiculite in charge.…”
Section: Crystal Chemical Structure Of Usmentioning
confidence: 79%
“…A significant conclusion from these data is that expandable interlayers in I/S from Ordovician K-bentonites with >15% swelling retain a smectitic character regardless of the proportion of illite, even after the particles have been disarticulated in suspension and resedimented on a laboratory substrate (Cetin and Huff, 1995). Moreover, there is not a close correlation between the magnitude of the interlayer charge and the proportion of swelling layers as determined by XRD.…”
Section: Layer Charge Of I/s In K-bentonitesmentioning
confidence: 81%
“…This is a method that utilizes the quantitative relationships between the layer charge and the area occupied by alkylammonium ions of varying carbon-chain lengths. Cetin and Huff (1995) studied a suite of Ordovician and Silurian K-bentonite clays with I/S interstratification ranging from R0 to R3 and containing between 30% and 97% illite layers. Since non-swelling clays such as illite are not responsive to short-term exchange reactions, only the swelling layers were examined.…”
Section: Layer Charge Of I/s In K-bentonitesmentioning
confidence: 99%
“…Srodon et al (1992) indicated a stable layer charge for smecrite in US from volcanic materials was about 0.80. Cetin and Huff (1995) have shown the average charge of smectite layers in I/S with expandability from 70% to 15% is 0.76, which is estimated by an alkylammonium ion exchange method. These values are similar to the ones we present.…”
Section: Discussionmentioning
confidence: 99%
“…These tests, for US samples, provide information for only expandable smectite layers in US. Recently, the charge of the expandable interlayers in US has been determined by the alkylammonium ion exchange method (Cetin and Huff 1995). It is possible to estimate the smectite-layer charge directly when the above tests are appropriately applied.…”
Section: Introductionmentioning
confidence: 99%